MATLAB-Assisted Dynamic Analysis and Balancing Optimization in Railway Wheel Sets - Kushawaha, Jeetender Singh (The Indonesian Institute of Science and Technology Research, 2025)
This study presents a MATLAB-assisted approach for dynamic analysis and optimization of balancing in railway wheel sets. By simulating multi-plane dynamic balancing equations, critical sources of imbalance were identified and mitigated. The methodology reduced counterbalancing weight consumption by 95.9%, achieving significant cost savings and operational efficiency in production trials. Factors such as wheel eccentricity and machine calibration were addressed comprehensively. This approach validates MATLAB as a cost-effective tool for industrial applications, with the provided code enabling adaptation in similar fields.